Ecological Doctors in Maasailand: Identifying Herding Best Practices to Improve Livestock Management and Reduce Carnivore Conflict - Jablonski, Kevin E.; Merishi, John; Dolrenry, Stephanie; Hazzah, Leela (Frontiers in Sustainable Food Systems, 2020)
Ilkisonko Maasai pastoralists in the Amboseli ecosystem of southern Kenya earn livestock-based livelihoods in a difficult environment exacerbated by a range of challenges. In this setting, many stakeholders, including the Maasai themselves, have come to see traditional extensive pastoralism as essential to long-term social–ecological resilience. This includes the maintenance of communal land tenure, which protects both unfragmented landscapes and the cultural practices necessary to thrive therein. This land tenure system has also been well-documented to support diverse wildlife populations, including large carnivores such as the African lion. Lion Guardians is a conservation organization working on the group ranches of the Amboseli ecosystem to reduce human–lion conflict using culturally appropriate strategies, with a 13-year track record of reductions in lion killing as compared to other conflict mitigation approaches. However, in recent years, they have noted a marked increase in the amount of lost livestock. Lion Guardians' data indicate that untended livestock account for >80% of lion attacks, making them a primary driver of human–lion conflict in the ecosystem. In this paper, we present the results of a community-based qualitative study aimed at identifying the causes of lost livestock, in pursuit of win–win solutions for people and lions. Using an iterative multistage research process, we conducted interviews with more than 120 Maasai community members. Finding general agreement that lost livestock are a problem and that poor herding practices are the primary cause, we next sought to identify both herder and herder-mentor best practices. For this, we focused on the knowledge of elders and “master herders,” those identified by their communities as especially adept and responsible herders. In creating these lists, we learned that herding best practices relevant to carnivore-conflict prevention are inseparable from those related to pasture management and livestock productivity and largely inseparable from traditional Maasai culture. This means that good herders, who have been called “ecological doctors,” can support the vitality of not only plants and pastures but also lions, ecosystems, and entire human cultures.